Childlike Parents in Guus Kuijer’s Polleke Series and Jacqueline Wilson’s The Illustrated Mum - Joosen, Vanessa (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
In this article, theories from age studies and children’s literature studies are combined to shed light on the construction of adulthood in books for young readers. The article begins with the sociological shift from a traditional model of adulthood with fxed benchmarks and increased commitment to a new ideal of fexibility in adulthood, as described by Harry Blatterer. It then explores how three acclaimed children’s books by Guus Kuijer and Jacqueline Wilson respond to this shift. The narratives all feature parents who display features that are explicitly labeled as “childlike” or that can be interpreted as diverging from the traditional model of “full” adulthood that Blatterer describes. As a result, the child protagonists are shown to experience stress and grief. Although the novels stress the playfulness of childlike adults as enjoyable, they ultimately promote a traditional model of responsible adulthood, even if few adult characters can actually live up to it.